(untitled) (Research, Society and Development, 2022)
Introduction: Orbital emphysema is considered a clinical condition characterized by the presence of air installed inadvertently in the orbital and/or periorbital region. Objectives: To describe a case of trauma to the face caused by compressed air with orbital and temporal emphysema in a pediatric patient. Case report: A 12-year-old male patient was admitted to the Oral and Maxillofacial Surgery and Traumatology Service of the Hospital da Restauração Governador Paulo Guerra – Recife/PE with trauma in the periorbital area after an accident with a compressed air jet. On physical examination, the patient presented slight right eyelid occlusion, edema, crepitation and symptoms on palpation. A computed tomography scan of the face was requested, showing signs suggestive of periorbital emphysema in the right orbit and in the right temporal region, as well as the absence of a fracture in the face. The patient was referred for ophthalmic evaluation, in which subcutaneous emphysema was confirmed in the subconjunctival, periorbital and right temporal region, with no impairment of visual acuity and ocular motility. We opted for conservative treatment with drug prescription and clinical follow-up. The patient remains under outpatient follow-up, with no sign of complications. Conclusions: Considering the absence of fracture and visual alteration, the conservative approach proved to be effective for the case described.